An Attenuated Adenovirus, ONYX-015, As Mouthwash Therapy for Premalignant Oral Dysplasia - Rudin, Charles M. (J Clin Oncol, 2003)
PURPOSE: Dysplastic lesions of the oral epithelium are known precursors of oral cancer. A significant proportion of oral dysplastic lesions have functional defects in p53 response pathways. The ONYX-015 adenovirus is selectively cytotoxic to cells carrying defects in p53-dependent signaling pathways. The current study sought to establish the feasibility and activity of ONYX-015 administered topically as a mouthwash to patients with clinically apparent and histologically dysplastic lesions of the oral mucosa. PATIENTS AND METHODS: A total of 22 patients (19 assessable patients) were enrolled onto the study. ONYX-015 was administered on three different schedules to consecutive cohorts. Biopsies of the involved mucosa were performed to evaluate histologic response and changes in expression of putative markers of malignant potential, including p53, cyclin D1, and Ki-67. Serology was performed to measure antiadenoviral titers. RESULTS: Histologic resolution of dysplasia was seen in seven (37%) of 19 patients, and the grade of dysplasia improved in one additional patient. The majority of responses were transient. No toxicity greater than grade 2 (febrile episode in one patient) was observed. Only one of seven patients demonstrated an increase in circulating antiadenoviral antibody titer while on therapy. Although responding and resistant lesions had similar mean p53 staining at baseline, histologic response correlated with a decrease in p53 positivity over time. Significant changes in cyclin D1 or Ki-67 were not observed. Viral replication was confirmed in two of three lesions examined. CONCLUSION: This novel approach to cancer prevention is tolerable, feasible, and has demonstrable activity.